Digital literacy communication model of ‘tular nalar’ curriculum during COVID-19 - Lestari, Puji; Kusmantini, Titik; Chandrasari, Yuli (Faculty of Communications Science, Dr. Soetomo University, 2021)
There are many hoaxes related to COVID-19 as shown in a pre-survey at the Citizens Association (RW) 69 Mitra Griya Asri (MGA Housing) Yogyakarta Family Welfare Empowerment (PKK) members, causing members of the WhatsApp group to feel uncomfortable and anxious. The purpose of this study was to evaluate three main aspects in the digital literacy communication model of Tular Nalar curriculum in RW 69 Mitra Griya Asri PKK members. This study used a qualitative evaluation research method with the following steps: 1) determining program objectives, 2) classifying objectives, 3) defining structured questions, 4) collecting data through simulation and interviews, and 5) documentation. Based on the results, RW 69 Mitra Griya Asri PKK members have understood digital literacy in the aspects of Tahu (Know), being Tanggap (responsive), and being Tangguh (resilient) in using digital media. Participants had eight (8) Tular Nalar digital literacy competencies, namely accessing information, managing information, designing messages, processing information, sharing messages, building self-resilience, protecting personal data, and collaboration. This study contributed to the form of Tular Reason curriculum evaluation as a new regulation in the socialization of digital literacy. This study also provides theoretical implications in the form of applying Gilster's Digital Literacy Theory by adding critical thinking specs, namely Tahu, being Tanggap, and being Tangguh in digital literacy